2013
DOI: 10.3945/ajcn.113.063032
|View full text |Cite
|
Sign up to set email alerts
|

Body composition from birth to 6 mo of age in Ethiopian infants: reference data obtained by air-displacement plethysmography

Abstract: By presenting z scores and centile reference charts for an apparently healthy urban Ethiopian infant population, this study represents a first step toward providing reference data on FM and FFM for an urban African context, which is important for future clinical care and research. This study was registered at www.controlled-trials.com as ISRCTN46718296.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 35 publications
4
73
1
2
Order By: Relevance
“…В одном из опубликованных исследований изучался компонентный состав тела, как у недоношенных, так и у доношенных детей, в течение 48 ч жизни, причем было проде-монстрировано, что количество жировой ткани у недоношенных детей, оцениваемой с помощью метода двухэнергетической аб-сорбциометрии (ДЭРА), достигало 13-14% [57]. Начиная с 2004 г. в клинической практике появилась возможность использовать приборы, в основе работы которых лежит принцип воздушной плетизмографии (ВПГ), что позволяет быстро, точно и неинва-зивно оценить компонентный состав тела у детей с массой тела от 1 до 8 кг [12,58,48]. Данный метод хорошо воспринимается ро-дителями детей и медицинскими работниками, а новорожденные неплохо переносят процесс обследования, что делает его весьма удобным для использования в клинических исследованиях.…”
Section: рисунок 2 центильные кривые параметров развития мальчиков вunclassified
“…В одном из опубликованных исследований изучался компонентный состав тела, как у недоношенных, так и у доношенных детей, в течение 48 ч жизни, причем было проде-монстрировано, что количество жировой ткани у недоношенных детей, оцениваемой с помощью метода двухэнергетической аб-сорбциометрии (ДЭРА), достигало 13-14% [57]. Начиная с 2004 г. в клинической практике появилась возможность использовать приборы, в основе работы которых лежит принцип воздушной плетизмографии (ВПГ), что позволяет быстро, точно и неинва-зивно оценить компонентный состав тела у детей с массой тела от 1 до 8 кг [12,58,48]. Данный метод хорошо воспринимается ро-дителями детей и медицинскими работниками, а новорожденные неплохо переносят процесс обследования, что делает его весьма удобным для использования в клинических исследованиях.…”
Section: рисунок 2 центильные кривые параметров развития мальчиков вunclassified
“…Furthermore, based on the same cohort, it was also shown that FFM was accreted linearly during the first 6 mo, whereas FM accretion leveled out at 4 mo of age (12). However, to our knowledge, the immediate and longterm health effects of postnatal BC accretion have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a follow-up of the iABC study, which involved a longitudinal birth BC cohort that has been described in detail elsewhere (12,21). In short, mothers and their newborns were recruited among mothers giving birth at the maternity ward in JUSH.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
See 2 more Smart Citations